THE IMPORTANCE OF ASSESSMENT IN THE LEARNING PROCESS - Tajieva, A.U.; Dawletmuratova, U.M. (SCIENCE and SOCIETY, 2025)
This article discusses the concept of assessment and its various definitions in different sources, and its importance in education. Nowadays, in Uzbekistan different types of assessment methods are being used in practice. The reason for utilizing new assessment types besides traditional assessment is to assess learners’ skills and make them better. Besides, the views of Asian and global researchers on the concept of assessment are also presented in the article. In particular, it discusses the stages, principles, and advantages of assessment in the educational process.